Queer Cinema in the World - Padva, Gilad (Historical Journal of Film, Radio and Television, 2019)
Karl Schoonover and Rosalind Galt’s Queer Cinema in the World initially proposes a radical comparative vision of cinema’s queer globalism. It aims to explore how queer filmmaking intersects with international sexual cultures, geopolitics, and aesthetics to disrupt dominant modes of world making.
_eprint: https://doi.org/10.1080/01439685.2019.1600882
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé